PET and PET/CT in radiation treatment planning for prostate cancer. Issue 7 (July 2011) - Pinkawa, Michael; Eble, Michael J; Mottaghy, Felix M
Molecular imaging by means of PET provides a method to study the metabolic activity of tumors in vivo . 18 F- or 11 C-choline and occasionally 18 F- or 11 C-acetate, are used as tracers for prostate cancer, reflecting the phospholipid metabolism. The hybrid technology PET/computed tomography significantly reduces image fusion mismatch. The role of molecular imaging is increasing in radiation treatment planning for prostate cancer. Local prostate cancer recurrence after primary radiation treatment usually originates at the location of the primary tumor. Focusing the dose escalation on the actual tumor is an option to increase tumor control without increasing toxicity. Image-guided radiotherapy and intensity-modulated radiotherapy are prerequisite technologies for applying the simultaneous boost concept. Clinical results are needed in the near future to support the effectiveness of the concept.